KAJIAN PERTUMBUHAN DAN HASIL BERBAGAI VARIETAS SELADA (Lactuca sativa) MENGGUNAKAN TEKNIK AQUAPONIK PADA KOLAM IKAN NILA DI DESA PESANTREN, WANAYASA, BANJARNEGARA - Rohman, Fathur; Rennanti Lunnadiyah Aprilia, (Nusantara Hasana Journal, 2025)
Lettuce (Lactuca sativa) is one of the horticultural commodities that has good prospects and commercial value. According to BPS data, Banjarnegara Regency has experienced an increase from 2021 to 2023. One way to increase lettuce production is by utilizing tilapia fish ponds using an aquaponics system. This technique also cultivates and harvests two commodities simultaneously, namely lettuce and tilapia fish. This research aims to determine the growth and yield of lettuce (Lactuca sativa) and to identify the suitable varieties for the aquaponic system. The research was conducted from December to January in the pesantren village. The method used is a Completely Randomized Design (CRD) non- factorial with one treatment, using five varieties of lettuce: Romaine, Siomak, Grand Rapid, Olga Red, and Captiva. The observational data were analyzed using SPSS software. If significant differences are found, further analysis using the DMRT 5% test will be conducted to determine the best treatment. The results of the study indicate that the best variety from the data is V3 (grand Rapid) with a high wet weight value of (99.06 grams), the highest dry leaf weight (2.58 grams), and the widest leaf area (51.01 cm2). V2 (Siomak) with a yield of 20.90 is significantly different and the highest from other treatments, indicating the greatest effect on plant height.